RELATIONSHIP OF EMPLOYMENT STATUS OF FIRST TRIMESTER PREGNANT WOMEN WITH ABORTION INCIDENCE AT AMINAH KRAKSAAN MATERNITY CLINIC - Mauliyatur Roifa; Iis Hanifah; Mega Silvian Natalia (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Work outside the home carried out by pregnant women, especially in the first trimester, is at risk of abortion, because the reproductive organs are not yet strong and the placenta is not fully formed. This study aims to analyze the relationship between the employment status of pregnant women in the first trimester and the incidence of abortion. This research is a correlational analytic study, while the research design is retrospective. Data were taken using medical records of patients who visited the Aminah Maternity clinic which was held in June-August 2022 with a total population and sample of 95 respondents taken by simple random. Data collection includes editing, coding and batching, then the data is analyzed manually and on a computer with the chi-square test. The results showed that the work status with heavy work had a greater incidence of abortion than 30 respondents with heavy work status, 29 people (96.7%) experienced an abortion and 1 person (3.3%) did not experience an abortion. This is supported by using the chi square test, namely the calculated X2 value is 19,591 > X2 table (2.60) meaning that there is a significant relationship between the Employment Status Relationship of First Trimester Pregnant Women with Abortion Incidence, and the Asymp value. Sig. (2-sided) 0.000 < 0.05 means that H0 is rejected and H1 is accepted. It is hoped that Aminah's maternity clinic can educate all patients to reduce strenuous activities during early pregnancy because young pregnancies are still prone to miscarriage